Nanocrystalline color conversion layer for MicroLED and preparation method of nanocrystalline color conversion layer
By combining thermal evaporation with magnetic mask technology, perovskite precursors and organic matrix materials are co-evaporated, solving the problems of thermal stability and patterning accuracy of nanocrystalline color conversion layers, realizing high-resolution full-color MicroLED displays, and improving color purity and color saturation.
Patent Information
- Application Number
- CN202511699812.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-01-20
AI Technical Summary
The poor thermal stability and insufficient patterning precision of the nanocrystalline color conversion layer in existing MicroLED display technology result in poor full-color display effects.
By employing thermal evaporation combined with magnetic mask technology, a nanocrystalline color conversion layer is directionally deposited at low temperature through co-evaporation of perovskite precursor and organic matrix material, and the mask structure is optimized to avoid material climbing and clogging, thereby achieving high-precision pixelated deposition.
It achieves high resolution and stable full-color display effect, increases the quantum yield of nanocrystalline fluorescence to over 85%, narrows the half-peak width to 20-30 nm, significantly improves color purity and color saturation, and is suitable for mass production.
Smart Images

Figure CN121368255A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of MicroLED display, in particular to a method for preparing a high-resolution nanocrystal color conversion layer by thermal evaporation combined with a magnetic mask, for realizing full-color MicroLED display. BACKGROUND
[0002] MicroLED display technology has become a research hotspot for the next generation of displays due to its excellent brightness, energy efficiency and stability, but its full-color implementation still faces major challenges. In the full-color display of MicroLED, there are two main problems: the massive transfer of red, green and blue LED chips integrated onto a substrate, and the efficiency reduction of red, green and blue LED chips as the chip size decreases. The full-color MicroLED display technology based on color conversion avoids the massive transfer problem and is not affected by the efficiency reduction of red, green and blue LED chips as the chip size decreases. Under the existing circumstances, the color conversion layer is the best solution for MicroLED to achieve full-color display.
[0003] Nanocrystals are a promising color conversion material in recent years due to their high fluorescence quantum yield, narrow emission half-width and large absorption coefficient. In the full-color display of MicroLED, a red, green and blue nanocrystal color conversion layer is deposited and aligned with MicroLED pixel points. The nanocrystals are excited by MicroLED to emit fluorescence, becoming a sub-pixel unit of three primary colors. In this process, requirements are often placed on the process and material of nanocrystals. On the one hand, the preparation process of nanocrystals requires pixelation and alignment with MicroLED; on the other hand, nanocrystals must maintain stable fluorescence peak position and intensity under long-term MicroLED excitation. Therefore, developing a new method for preparing a nanocrystal color conversion layer for MicroLED will greatly improve the difficulties of MicroLED display technology. SUMMARY
[0004] Therefore, the present application proposes a nanocrystal color conversion layer preparation method based on thermal evaporation combined with a mask, to address the poor thermal stability of nanocrystals and insufficient patterning accuracy in existing MicroLED color conversion layer preparation techniques. This method co-evaporates nanocrystals and organic matrix materials to achieve high-precision pixelation deposition while avoiding thermal decomposition of nanocrystals. An optimized mask structure and evaporation process are used to effectively suppress material wall climbing and mask clogging, ensuring micron-level pattern resolution and achieving high-resolution and stable full-color display effects.
[0005] To achieve the above purpose, the present application adopts the following technical solutions:
[0006] The first aspect of the present application provides a nanocrystal color conversion layer for MicroLED, which is formed by co-evaporating a perovskite precursor (ABX3, A=Cs / MA / FA / PEA, B=Pb / Sn / Cu, X=Cl / Br / I) with an organic matrix material containing P=O / S=O / C=O groups, and then depositing the nanocrystal color conversion layer through mask openings at a low temperature of 150-400℃.
[0007] Optionally, the molar ratio of nanocrystals to matrix material in the nanocrystal color conversion layer is 1:0.1-1:2.
[0008] The precursor material is selected from at least one of CsCl, CsBr, CsI, MABr, MAI, FABr, FAI, PEABr, PEAI, and PbCl2, PbBr2, PbI2, SnCl2, SnBr2, SnI2, CuCl, CuBr, and CuI.
[0009] The matrix material is an organic material with an evaporation temperature ≤350℃ at 2×10 -4 Pa, and contains one or more P=O, S=O, and C=O groups.
[0010] Further, the matrix material is selected from one or more combinations of triphenylphosphine oxide, tris(4-fluorophenyl)phosphine oxide, tris(4-methoxyphenyl)phosphine oxide, (o-fluorophenyl)diphenylphosphine oxide, stearic acid (C 18 H 36 O2), benzophenone (C 13 H 10 O), diphenyl sulfone (C 12 H 10 O2S), and p-toluenesulfonamide (C7H9NO2S).
[0011] The second aspect of the present application provides a preparation method of the nanocrystal color conversion layer for MicroLED as described above, which comprises the following steps:
[0012] 1) Using a patterned mask to adhere to the MicroLED substrate, and the mask openings correspond to the pixel unit positions.
[0013] 2) Using the nanocrystal precursor and one or more matrix materials as the evaporation source, heating the evaporation source to 150-400℃ in the vacuum chamber, so that the precursor+matrix composite material is deposited on the MicroLED pixels through the mask openings, and the nanocrystal color conversion layer is formed by evaporation reaction.
[0014] Optionally, the evaporation rate of the precursor material is 0.01-5 nm / s, the thickness of the color conversion layer is 500-3000 nm, the interfacial roughness Ra is less than 10 nm, and the molar ratio of the nanocrystals to the matrix material in the color conversion layer is 1:0.1-1:2.
[0015] Optionally, the mask used is a magnetic metal mask with a thickness of 20-200 μm, the opening sidewall has an inclination angle of 45-85°, and the sidewall is coated with a polytetrafluoroethylene (PTFE) coating; the magnetic attraction of the mask is 0.1-0.5 N / cm², and mechanical contact damage is ensured when the distance between the mask and the substrate is ≤0.2 mm.
[0016] Optionally, the precursor material is selected from at least one of CsCl, CsBr, CsI, MABr, MAI, FABr, FAI, PEABr, PEAI, and PbCl2, PbBr2, PbI2, SnCl2, SnBr2, SnI2, CuCl, CuBr, and CuI; the matrix material is an organic material with a boiling point of ≤350℃ at 1 Pa, and contains one or more P=O, S=O, and C=O groups. -4 Pa, and contains one or more P=O, S=O, and C=O groups.
[0017] Further, the matrix material is selected from one or more combinations of triphenylphosphine oxide, tri(4-fluorophenyl)phosphine oxide, tri(4-methoxyphenyl)phosphine oxide, (o-fluorophenyl)diphenylphosphine oxide, stearic acid (C 18 H 36 O2), benzophenone (C 13 H 10 O), diphenyl sulfone (C 12 H 10 O2S), and p-toluenesulfonamide (C7H9NO2S).
[0018] Optionally, during the evaporation process, the dynamic vacuum degree in the vacuum chamber is 5×10 -4 ~5×10 -5 Pa.
[0019] Optionally, the preparation method further comprises: performing an annealing treatment at 50-100℃ for 3-30 minutes after deposition.
[0020] It should be noted that the color conversion layer is attached to the MicroLED to achieve full-color display in a wide color gamut range, wherein the color coordinates of red light are x≥0.70, y≤0.30; and the color coordinates of green light are x≤0.15, y≥0.75.
[0021] Compared with the prior art, the nanocrystal color conversion layer for MicroLED and the preparation method thereof provided by the present disclosure have the following beneficial effects:
[0022] 1. The thermal evaporation technology is derived from the mature OLED industry, and the equipment and process are highly standardized, which can be directly connected to the existing MicroLED production line, and the yield is > 95%.
[0023] 2. The patterning precision of mask evaporation can be as low as 2-5 μm, and by optimizing the mask temperature and inclination angle design, the material blockage problem is avoided, which is suitable for large-scale repetitive preparation.
[0024] 3. Through the low-temperature co-evaporation process, the fluorescence quantum yield of nanocrystals can be improved to more than 85%, and the half peak width (FWHM) is as narrow as 20-30 nm, which significantly improves the color purity and color saturation (NTSC color gamut > 120%) of MicroLED display.
[0025] 4. The introduction of organic matrix material effectively inhibits the oxidation and ion migration of nanocrystals, and improves the working stability of the nanocrystal color conversion layer. BRIEF DESCRIPTION OF DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application or the prior art, the drawings needed to be used in the embodiment or prior art description will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present application, and those skilled in the art can obtain other drawings according to the provided drawings without creative labor.
[0027] Figure 1 is a schematic diagram of depositing perovskite color conversion layer with mask plate.
[0028] Figure 2 is the optimization effect after depositing the color conversion array after the design of the mask plate and process optimization.
[0029] Figure 3 is the front and back microscope photos of the designed mask plate before and after evaporation without hole blockage.
[0030] Figure 4 is the microscope picture and fluorescence picture of the color conversion layer prepared in embodiment 1 of the present application.
[0031] Figure 5 is the fluorescence picture of the color conversion layer prepared in embodiment 2 of the present application.
[0032] Figure 6 is the fluorescence picture of the color conversion layer prepared in embodiment 3 of the present application. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application.
[0034] Herein, the term "embodiment" is not necessarily interpreted as superior or better than other embodiments as any embodiment described as "exemplary". In the performance index test of the embodiments of the present application, unless otherwise specified, the conventional test method in the art is adopted. It should be understood that the terms described in the present application are only for describing the specific embodiments, and are not used to limit the disclosure of the present application.
[0035] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the present application belongs; and the test methods and technical means not specially noted in the present application refer to the experimental methods and technical means commonly used by those skilled in the art.
[0036] In the description of the present application, it should be understood that the terms "middle", "upper", "lower", "rise", "fall", "vertical", "surface", "top", "bottom", "inner", "outer" and the like indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a particular orientation, be constructed and operated in a particular orientation, and therefore cannot be understood as a limitation on the present application.
[0037] In order to better illustrate the content of the present application, a large number of specific details are given in the specific embodiments below. Those skilled in the art should understand that the present application can also be implemented without some specific details. In the embodiments, some methods, means, instruments, devices and the like which are well known to those skilled in the art are not described in detail, in order to highlight the main idea of the present application.
[0038] The technical features disclosed in the embodiments of the present application can be combined in any way without conflict, and the technical solutions obtained by combination belong to the disclosure of the embodiments of the present application.
[0039] The present application discloses a preparation method of a nanocrystal color conversion layer for MicroLED.
[0040] In order to better understand the technical solutions of the present application, the preparation method and working principle thereof will be described in detail below in combination with specific embodiments. It should be understood that the embodiments are only used to illustrate the present application, and are not used to limit the scope of protection of the present application.
[0041] Embodiment 1
[0042] (1) MicroLED substrate preparation: use a nitrogen gun to blow clean the dust on the MicroLED substrate, place the MicroLED substrate in a tray, and tightly attach a 200 μm thick mask with an opening angle of 83° to the tray;
[0043] (2) Co-evaporation of precursors + matrix material: CsBr, PbBr2 and triphenylphosphine oxide were separately loaded into a quartz crucible, the vacuum degree of the vacuum chamber was lowered to 2 x 10 -4 Pa, and then the precursors and matrix material were heated. When the evaporation rates of CsBr, PbBr2 and triphenylphosphine oxide reached 0.1 nm / s, 0.1 nm / s and 0.04 nm / s respectively and stabilized, the substrate shutter was opened to deposit the color conversion layer.
[0044] Example 2
[0045] (1) MicroLED substrate preparation: use a nitrogen gun to blow clean the dust on the MicroLED substrate, place the MicroLED substrate in a tray, and tightly attach a 200 μm thick mask with an opening angle of 83° to the tray;
[0046] (2) Co-evaporation of precursors + matrix material: CsBr, PbI2 and (o-fluorophenyl) diphenylphosphine oxide were separately loaded into a quartz crucible, the vacuum degree of the vacuum chamber was lowered to 2 x 10 -4 Pa, and then the precursors and matrix material were heated. When the evaporation rates of CsBr, PbI2 and (o-fluorophenyl) diphenylphosphine oxide reached 0.1 nm / s, 0.1 nm / s and 0.04 nm / s respectively and stabilized, the substrate shutter was opened to deposit the color conversion layer.
[0047] (3) Annealing treatment: the deposited color conversion layer was placed on a hot stage at 50°C and annealed for 3 minutes.
[0048] Example 3
[0049] (1) MicroLED substrate preparation: use a nitrogen gun to blow clean the dust on the MicroLED substrate, place the MicroLED substrate in a tray, and tightly attach a 200 μm thick mask with an opening angle of 83° to the tray;
[0050] (2) Co-evaporation of precursors + matrix material: CsCl, PbBr2 and triphenylphosphine oxide were separately loaded into a quartz crucible, the vacuum degree of the vacuum chamber was lowered to 2 x 10 -4 Pa, and then the precursors and matrix material were heated. When the evaporation rates of CsCl, PbBr2 and triphenylphosphine oxide reached 0.1 nm / s, 0.1 nm / s and 0.04 nm / s respectively and stabilized, the substrate shutter was opened to deposit the color conversion layer.
[0051] Depend on Figures 1-2 It is known that designing the opening angle of the mask can reduce the shading effect during high-resolution deposition of nanocrystal arrays and improve the uniformity of the array.
[0052] Depend on Figure 3 It is known that a reasonable mask design is beneficial for multiple depositions of nanocrystal arrays without causing blockage.
[0053] Depend on Figures 4-6 It is known that the nanocrystal array prepared by the present invention can emit green fluorescence, red fluorescence and blue fluorescence, and has good uniformity.
[0054] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A nanocrystal color conversion layer for a MicroLED, characterized in that, The nanocrystal color conversion layer is formed by co-evaporation of perovskite precursor (ABX3, A=Cs / MA / FA / PEA, B=Pb / Sn / Cu, X=Cl / Br / I) and organic matrix material containing P=O / S=O / C=O groups, and is deposited through mask openings at a low temperature of 150-400°C.
2. The nanocrystal color conversion layer for MicroLED of claim 1, wherein, The molar ratio of nanocrystal to matrix material in the nanocrystal color conversion layer is 1:0.1-1:
2. The precursor material is selected from at least each of CsCl, CsBr, CsI, MABr, MAI, FABr, FAI, PEABr, PEAI, and PbCl2, PbBr2, PbI2, SnCl2, SnBr2, SnI2, CuCl, CuBr, and CuI. Matrix material is an organic material with a vaporization temperature < 350°C at 2 x 10 -4 Pa, containing one or more P=0, S=0, C=0 groups.
3. The nanocrystal color conversion layer for MicroLED of claim 2, wherein, The matrix material is selected from one or more of a combination of triphenylphosphine oxide, tri(4-fluorophenyl)phosphine oxide, tri(4-methoxyphenyl)phosphine oxide, (o-fluorophenyl)diphenylphosphine oxide, stearic acid (C 18 H 36 O2), benzophenone (C 13 H 10 O), diphenyl sulfone (C 12 H 10 O2S), p-toluenesulfonamide (C7H9NO2S).
4. The method of claim 1, wherein the method is performed by a process comprising: The method comprises the following steps: 1) Use a patterned mask to adhere to the MicroLED substrate, and the mask openings correspond to the pixel unit positions; 2) Use the nanocrystal precursor and one or more matrix materials as evaporation sources, heat the evaporation sources to 150-400°C in a vacuum chamber, and make the precursor+matrix composite material deposit through the mask openings on the MicroLED pixels, and evaporate to form a nanocrystal color conversion layer.
5. The method of claim 4, wherein the method further comprises: The evaporation rate of the precursor material is 0.01-5 nm / s, the thickness of the color conversion layer is 500-3000 nm, the interlayer interface roughness Ra is less than 10 nm, and the molar ratio of nanocrystal to matrix material in the color conversion layer is 1:0.1-1:
2.
6. The method of claim 4, wherein the method further comprises: The mask used is a magnetic metal mask with a thickness of 20-200 μm, an opening side wall inclination angle of 45-85°, and a side wall coated with a polytetrafluoroethylene (PTFE) coating; The magnetic attraction of the mask is 0.1-0.5 N / cm², and mechanical contact damage is prevented when the distance between the mask and the substrate is ≤0.2 mm.
7. The method of claim 4, wherein the method further comprises: The precursor material is selected from at least each of CsCl, CsBr, CsI, MABr, MAI, FABr, FAI, PEABr, PEAI, and PbCl2, PbBr2, PbI2, SnCl2, SnBr2, SnI2, CuCl, CuBr, and CuI. Matrix material is an organic material with a vaporization temperature < 350°C at 2 x 10 -4 Pa, containing one or more P=0, S=0, C=0 groups.
8. The method of claim 7, wherein the method further comprises: The matrix material is selected from one or more of a combination of triphenylphosphine oxide, tri(4-fluorophenyl)phosphine oxide, tri(4-methoxyphenyl)phosphine oxide, (o-fluorophenyl)diphenylphosphine oxide, stearic acid (C 18 H 36 O2), benzophenone (C 13 H 10 O), diphenyl sulfone (C 12 H 10 O2S), p-toluenesulfonamide (C7H9NO2S).
9. The method of claim 4, wherein the method further comprises: During evaporation, the dynamic vacuum in the vacuum chamber was 5 x 10 -4 Pa. During deposition, the dynamic vacuum in the vacuum chamber was 5 x 10 -5 Pa.
10. The method of claim 4, wherein, The method further comprises: After deposition, an annealing treatment at 50-100°C is performed for 3-30 minutes.